The Rev Counter Decision - Moore, P. G. (Institutional Knowledge at Singapore Management University, 1973)
This case-based article arose out of a decision tree analysis carried out by the authors in an industrial firm. The company's identity and the actual product manufactured have both been altered for reasons of confidentiality. The various discussions outlined in the case are reported in the same order as they occurred within the firm whilst the problem was originally under study. The work reported was first carried out in 1971 and has been the subject of regular "follow-up" analyses since that date. A much simplified and restricted version of Parts I and II of this case was originally published in two articles appearing in the Financial Times during January 1972.